Comparison of standard T2-weighted turbo spin echo and volumetric interpolated breath-hold examination magnetic resonance imaging sequences in the assessment of articular process dysplasia in Pug dogs with thoracolumbar myelopathy - Gilbert, Emma; Rose, Jeremy; Arrol, Lorna; Driver, Colin J. (Frontiers in Veterinary Science, 2023)
A retrospective study to compare the classification of thoracic (T10-T13) caudal articular process (CAP) morphology in Pug dogs with a thoracolumbar myelopathy as normal, hypoplastic or aplastic, between T2 weighted Turbo Spin Echo (T2W-TSE), in sagittal and transverse planes, and Volumetric Interpolated Breath-hold Examination (VIBE) Magnetic Resonance Imaging (MRI) sequences, in comparison to Computed Tomography (CT). We hypothesized a stronger agreement for VIBE in comparison to T2W-TSE. Diagnostic accuracy of T2W-TSE was inferior to VIBE for aplastic (60%, 95% CI 0.561 -0.639) versus 78%, 95%CI 0.744 -0.815) hypoplastic (44%, 95%CI 0.427 -0.452 versus 62.5%, 95%CI 0.595 -0.655) and normal CAP (70%, 95%CI 0.655 -0.744 versus 87% 95%CI 0.848-0.892). Superior accuracy of classification using VIBE versus T2W-TSE sequences using the McNemar Chi squared test was significant for aplastic (p= 0.0002) and normal CAP (p=0.004). VIBE sequences had a sensitivity of 96% and specificity of 75% to detect CAP abnormality and with T2W-TSE imaging sensitivity 81% and specificity of 75%. Threedimensionally reconstructable VIBE sequences were significantly more accurate than traditional T2W-TSE MRI sequences in classifying CAP morphology, which should reduce the need for CT for pre-operative assessment.